Debt Bias and Other Distortions : Crisis-Related Issues in Tax Policy. (Policy Papers; Policy Paper, 2009)
Tax distortions are likely to have encouraged excessive leveraging and other financial market problems evident in the crisis. These effects have been little explored, but are potentially macro-relevant. Taxation can result, for example, in a net subsidy to borrowing of hundreds of basis points, raising debt-equity ratios and vulnerabilities from capital inflows. This paper reviews key channels by which tax distortions can significantly affect financial markets, drawing implications for tax design once the crisis has passed.